INTELLIGENCE DISCIPLINE AT THE AGE OF PRE-SCHOOL KIDS - Shamsuddinova Diyoraxon Yorqinbek qizi; Qodirova Mohlaroyim Ravshanbek qizi (TADQIQOTLAR, 2025)
Annotation: This article explores the concept of intelligence discipline among preschool  children  and  how  it  shapes  their  cognitive,  emotional,  and  social development.  It  focuses  on  the  significance  of  nurturing  self-regulation,  attention control, and problem-solving skills during early childhood. Through a methodological analysis of psychological and pedagogical approaches, the paper emphasizes the role of parents and educators in guiding children's discipline without suppressing creativity or curiosity.